2020
DOI: 10.7150/ijms.46339
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Global Gene Expression and Complement Components Levels in Umbilical Cord Blood from Preterm and Term Neonates: Implications for Significant Downregulation of Immune Response Pathways related to Prematurity

Abstract: Background: Preterm birth is the most frequent cause of neonatal death, but its aetiology remains unclear. It has been suggested that the imbalance of immunological mechanisms responsible for maintaining pregnancy is contributing to preterm birth pathogenesis. We aimed to investigate global gene expression and the levels of several complement system components in umbilical cord blood samples from preterm neonates and compare them to term newborns. We sought to examine how differentially expressed ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Several studies have described that umbilical cord blood samples from preterm infants showed downregulation of immune pathways, including complement cascades in infants and upregulation in maternal blood, which may imply that besides lung barrier integrity, immune responses might be reduced in preterm neonates 38,39 . Regarding the molecular sensors of innate immunity in premature infants, previous publications describe that TLR4 and TLR2 receptors are reduced in animals, impairing neutrophil recruitment, while neutrophils from neonates themselves show impaired migration, phagocytosis and cytotoxic activity [40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described that umbilical cord blood samples from preterm infants showed downregulation of immune pathways, including complement cascades in infants and upregulation in maternal blood, which may imply that besides lung barrier integrity, immune responses might be reduced in preterm neonates 38,39 . Regarding the molecular sensors of innate immunity in premature infants, previous publications describe that TLR4 and TLR2 receptors are reduced in animals, impairing neutrophil recruitment, while neutrophils from neonates themselves show impaired migration, phagocytosis and cytotoxic activity [40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…C9 deposition increases at the implantation sites in pregnant mice with fetal loss (69). C9 concentration is enhanced in the umbilical cord blood of term infants, which is associated with its role in immunity in prematurity (70). Therefore, it is suggested that the upregulation of C9 in maternal lymph nodes at day 16 of pregnancy may be associated with placentation, and the downregulation of C9 at day 25 of pregnancy may be beneficial for pregnancy maintenance in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure using previously described methods [ 47 , 48 ] started with a poly(A) tailing reaction followed by ligation of the biotinylated signal molecule to the target RNA. The next step was sample hybridization onto an Affymetrix miRNA 4.1 Array Strip (Affymetrix, Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%